Influence of Bubble Deformation on the Signal Characteristics Generated Using an Optical Fiber Gas–liquid Two-Phase Flow Sensor - Yu Ma (MDPI AG, 2021)
The use of optical fiber probe in two-phase flow measurements is very frequently encountered, especially in the applications of chemical engineering and petroleum industries. In this work, the influence of bubble piercing signals caused by bubble deformation is studied experimentally using a laboratory-prepared wedge-shaped fiber probe in a lab-scale gas–liquid flow generator. A three-dimensional simulation model is established to study the influence of bubble deformation on the piercing signals. A theoretical analysis of the characteristics of the pre-signal influenced by the bubble deformations is undertaken for a wide range of different modeled bubble shapes. Combining the experimental and simulation results, a promising analytical method to estimate the bubble shapes by analyzing the characteristics of pre-signals is proposed. The results of this investigation demonstrate that it is possible to estimate the bubble shapes before the fiber probe contacts the bubble surface. The method developed in this investigation is therefore highly promising for reducing errors caused by deformation during the probe piercing process.